Aplikasi Android pencarian jasa titip dari traveller yang bepergian di dalam dan luar negeri - Billy Sugiharto; Henry Novianus Palit; Djoni Haryadi Setiabudi (Jurnal Infra, 2021)
In several social media applications such as Facebook and Instagram, a traveler who is traveling (both local and international) is often found offering services to purchase goods for a certain fee. This has even become a permanent source of income for some of them. However, this has several problems, both from the buyers and the traveler's side. From the buyer's side, it would be very risky because they have to transfer money first. From the traveler's point of view, social media is not a place only to look for entrusted services so that their chances of getting buyers will not be maximized. From the existing problems, an Android-based application was made to collect these travelers so that prospective buyers know where to go when looking for a entrusted service. Similar applications used for comparison include the UShopper application[1], the X application[3], the Y application[2], Bistipand Airfrov. In the application above, no one applies the fair review feature and only the Bistip application has a chat feature between users before carrying out the transaction process.The application created solves the mentioned issues by applying a fair review system so that there are no biased reviews and has a chat feature so that users can communicate with each other without having to use other applications.Based on the results of tests that have been carried out through a questionnaire with 8 respondents who have played a role as a buyer in a entrusted service, the application that was made received an average score of 4,625 out of 5. The application is considered to be able to help prospective buyers find the right traveler according to their wishes with the help of features filtering. This feature can filter travelers that buyers are looking for with parameters: maximum return date and types of items that can be brought on a trip.